The Role of School Administration in Translating Professional Training into Classroom Practices: A Study on Primary School Teachers in Riyadh (The International Journal for Scientific Research, 2025)
This study investigates the role of school administration in supporting teachers' implementation of classroom practices gained from professional training programs in primary schools in Riyadh. Using a quantitative approach, simple linear regression analysis was conducted to test the main and sub-hypotheses. The results revealed a statistically significant and strong positive relationship between the role of school administration and teachers’ application of the learned practices, affirming the main hypothesis. Among the sub-dimensions, educational leadership had the strongest impact (B = 0.55), followed by support for professional learning communities (B = 0.48), and creating a supportive school environment (B = 0.43). These findings emphasize the pivotal role of school leaders in translating training into effective classroom practices by fostering a supportive environment and facilitating collaboration among teachers. The study recommends enhancing school leaders' competencies, activating professional learning communities, and aligning training with teachers’ real needs to ensure sustainable improvement in teaching quality. Future research should explore the role of school administration across different educational stages and examine contextual factors that influence the application of training outcomes.
Keywords: School leadership; Professional development; Classroom practices; Instructional leadership; Professional learning communities; School environment; Primary schools